2019
DOI: 10.1021/acs.jpca.9b09085
|View full text |Cite
|
Sign up to set email alerts
|

Non-condon Effect on Ultrafast Excited-State Intramolecular Proton Transfer

Abstract: The reaction dynamics of excited-state intramolecular proton transfer (ESIPT) of 2,2′-dihydroxyazobenzene (2,2′-DHAB) was investigated by means of white-light supercontinuum femtosecond transient absorption spectroscopy. A coherent in-phase oscillation was observed in the entire wavelength range where stimulated emission of the photoproduct is dominant. This result indicates that the transition strength of the product state is dynamically modulated by a nuclear wavepacket motion (non-Condon effect). The observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…However, it has to be noted that the N−H or O−H stretching may not be directly involved in the ESIPT reactions, but those vibrational modes that are associated with the changes of the H-bond in distance and/ or angle. 39,86 Therefore, our calculation may not directly reflect the experimental observation, due mainly to the multiple dimensional reaction coordinates that cannot be fully considered at this stage. Overall, these results indicate that the ESIPT kinetics and thermodynamics are strongly correlated in the PBTs derivatives.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, it has to be noted that the N−H or O−H stretching may not be directly involved in the ESIPT reactions, but those vibrational modes that are associated with the changes of the H-bond in distance and/ or angle. 39,86 Therefore, our calculation may not directly reflect the experimental observation, due mainly to the multiple dimensional reaction coordinates that cannot be fully considered at this stage. Overall, these results indicate that the ESIPT kinetics and thermodynamics are strongly correlated in the PBTs derivatives.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Among a variety of H-bond associated research directions, one field should be credited to the proton transfer reaction in the electronically excited state. Upon photoexcitation, driven by the changes of the acidity and basicity in the excited state, the transfer of a proton from the OH or NH proton-donating site to the O or N proton-accepting site becomes feasible. When it takes place within the molecular unit, the process is dubbed as the excited-state intramolecular proton transfer (ESIPT), which has been receiving considerable attention in both fundamental and applied researches. On the one hand, the result of ESIPT forms a proton-transfer isomer, namely, the tautomer, in the excited state, which does not exist in the ground state thermally and accordingly gives rise to an anomalously large Stokes shift emission (cf. the non-proton transfer, normal emission).…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that optical excitation can directly prepare the electron–proton transfer photoproduct . However, it is important to note that all of these previous time-resolved spectroscopic studies have regarded the photoinduced PCET reaction as a state-to-state transition. , However, contrary to this treatment, electronically excited states are typically best described via mixing of different electronic configurations, and the degree of mixing can change throughout the course of the movement of electrons and protons. , Moreover, photoexcitation leads a system into a nonequilibrium distribution of many vibronic energy levels . For the above reasons, the mechanism of ultrafast photoinduced PCET remains essentially unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…16,19−21 However, contrary to this treatment, electronically excited states are typically best described via mixing of different electronic configurations, and the degree of mixing can change throughout the course of the movement of electrons and protons. 22,23 Moreover, photoexcitation leads a system into a nonequilibrium distribution of many vibronic energy levels. 24 For the above reasons, the mechanism of ultrafast photoinduced PCET remains essentially unexplored.…”
Section: ■ Introductionmentioning
confidence: 99%